Authority of the Indonesian Doctors Association (IDI) in Providing Recommendations for Medical Practice Permits - Gunawan, Rudi; Helvis, Helvis (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The law says that doctors and dentists have the right to perform medical actions because their jobs are unique. A doctor who does not obtain consent for legal medical action and/or performs medical practices that are not in accordance with professional standards violates human rights and health. Violations of the right to health are also violations of human rights. The goal of this study is to examine the authority of the Indonesian Doctors Association (IDI), a professional organization that provides recommendations for the issuance of licenses to practice for doctors practicing in Indonesia, and how it, along with the Indonesian Medical Council (KKI), contributes to the maintenance and promotion of the professionalism and ethics of its members (the medical profession). The approach used in this study is a normative legal approach that focuses on the results of positive legal research. As for the results of this study, cooperation between the professional organization of the Indonesian Doctors Association (IDI) and the Central Government and Regency/City Regional Governments for medical practice licensing services and supervisory boards is needed to maintain the professionalism of IDI as the only professional doctor organization in Indonesia.